REACTION OF BT COTTON HYBRIDS AGAINST MAJOR DISEASES - S. L. BHATTIPROLU and V. CHENGA REDDY (The Journal of Research ANGRAU, 2017)
One hundred and twelve(112) Bt cotton hybrids were evaluated during kharif 2013 and 2014, in randomized block design with two replications, each composed of four rows, at a spacing of 105 cm x 60 cm. Infector row technique was employed to supplement the natural disease pressure and intensity of Alternaria leaf spot, grey mildew and rust was recorded by adopting 0 to 4 scale. Bt hybrid, Ankur 2224 was free from grey mildew and moderately resistant to Alternaria leaf spot (ALS) while Ankur Shreyash was resistant to grey mildew (GM) and moderately resistant to ALS and rust. Bt hybrid, ACH 152-2 showed resistant reaction to both ALS and GM. Bt hybrid, Ankur 8120 exhibited resistance to rust and moderate resistance to GM. Two Bt hybrids viz., Bio 7213-2 and RJHH 10 were moderately resistant to ALS, GM as well as rust. Sixteen Bt hybrids were moderately resistant to ALS and GM, whereas, nine Bt hybrids were moderately resistant to ALS and rust. Seven Bt hybrids expressed moderately resistant reaction to both GM and rust. These studies help cotton farmers, in particular, small and marginal as well as tenant farmers to choose best Bt hybrids with multiple disease resistance for ecofriendly and economic production.